Selectivity of herbicides in initial growth of pre-budded seedlings of sugarcane - Silva Junior, Antonio Carlos; Dias, José Luiz Carvalho de Souza; Martins, Dagoberto (Comunicata Scientiae, 2018)
With the advent of new implantation technologies of sugarcane crop, the aim of this study was to evaluate the selectivity of herbicides in pre-budded cultivars of sugarcane seedlings. With the formation of seedlings from a gem of high sanity in tubes with substrates, seedlings, with an average height of 20 cm, were transplanted to 12 L pots filled with soil. The experimental design was a completely randomized factorial arranged in a (3x8), being the cultivars, CTC 7, CTC 14 and RB966928; and the herbicides (g ha-1): ametryn + trifloxysulfuron-sodium (1280 + 32.4); imazapic (150); halosulfuron (150); isoxaflutole (90); ametryn (5000); ametryn + clomazone (1500 + 1000) and amicarbazone (1500), applied 10 days after transplanting; and a control without application. The three cultivars of sugarcane visually studied responded differently to the application of herbicide treatments tested, being the herbicides ametryn + trifloxysulfuron, imazapic, halosulfuron and ametryn which caused less phytotoxicity. However, when confronting the other parameters analyzed, it was observed that ametryn + trifloxysulfuron, isoxaflutole, ametryn, ametryn + clomazone and amicarbazone for CTC7 cultivar, ametryn + clomazone and amicarbazone for CTC14 and amicarbazone for RB966928, caused loss to the initial development of the crop.